New zeolite-based composite pads with high-volume blood absorption for early warning of postpartum hemorrhage - Sulastri, Sulastri; Siregar, Tongku N.; Adlim, Muhammad; Hasanuddin, Hasanuddin; Muktaridha, Muktaridha (Narra J, 2024)
Medical treatment of severe blood loss during labor is crucial, and the early warning indicator of postpartum hemorrhage (PPH) is essential for labor medical treatment. Measurement of blood loss conventionally looks dirty, reluctant, and less hygienic since some of the blood might be spilled out in the maternity bed, while commercially existing pads have low blood absorption capacity. A new design composite pad composed of absorbent materials including cellulose rayon, super absorbent polymer (SAP), and zeolite was fabricated and characterized. The SAP and zeolite show properties as crystalline and amorphous materials, respectively. The surface area of natural zeolite was 19.79 (m2/g). The newly fabricated composite pad showed a high blood absorption capacity (>500–600 mL) with a blood absorption rate of 55.56–85.84 mL/min (depending on the blood volume), showing better performance as compared to the commercial pads. These characteristics suggest that the new composite pad could function not only as a sanitary pad but also as an early warning indicator for PPH if the rate and blood volume reach the dangerous category (≥600 mL or at ≥13 mL/min rate).